Databook of the most important polymer and rubber additives - Wypych, Anna; Wypych, George (ChemTec Publishing, 2024)
"This book is a comprehensive reference for anyone working with polymers and rubber. It provides information on the properties of the most important additives that can be used to alter the physical, chemical, and mechanical properties of rubber and plastics."--